Kreativ scenekunstpolitik - Hansen, Louise Ejgod (Peripeti, 2011)
Creative Performing Arts Policy The article analyses the report Performing Arts in Denmark: Roads to development and the comments gathered through the public hearing process with the purpose of discussing the concept of artistic development. By using theories about creativity, the article argues for a more nuanced understanding of how artistic development can be stimulated by cultural political means.